Evaluation of a new histological grading system for assessing the response to chemotherapy of peritoneal metastases from colorectal cancer: A mouse model study. Issue 1 (January 2020) - Taibi, Abdelkader; Lo Dico, Rea; Kaci, Rachid; Naneix, Anne laure; Malgras, Brice; Mathonnet, Muriel; Pocard, Marc
Abstract: This experimental study evaluated the histological response of peritoneal metastases (PM) from colorectal cancer (CRC) after preoperative systemic chemotherapy (pCT). The results demonstrated that the Peritoneal Regression Grade Score could be used in medical practice. Aim: The aim was to evaluate the histological criteria used by the tumour regression grade (TRG) and Peritoneal Regression Grade Score (PRGS) for determining the response to chemotherapy (CT), in a mouse model of peritoneal metastases (PM) from colorectal cancer (CRC). Methods: Twenty immunocompetent BALB/c mice were randomized into four groups at day (D) 10 after intraperitoneal (ip) injection with bioluminescent CRC tumour cells (CT26-luc). A histology before treatment group was obtained by sacrifice on D10; the other groups all received one of the following ip treatments over 15 days: 5% glucose (control, G5); 5-fluorouracil (5FU, 0.03 mg/g); or 5FU with oxaliplatin (Ox, 0.006 mg/g). The histological response (HR) was analysed by comparing the histology of PM before and after treatment, using both scores: TRG and PRGS. Results: All mice showed limited PM as visualised by bioluminescence and confirmed at the time of sacrifice in the histology before treatment group. The mean peritoneal carcinomatosis index (PCI) was = 8 [6–10], The rate of complete HR was significantly higher in the Ox-5FU group (83.3%) than 5FU group (0%) and G5 group (0%) (p = 0.016). Fibrosis was present only in CT-treated groups (p = 0.05). PCI, ascites volume and haemorrhagic ascites were significantly higher in the G5 group than CT groups (p < 0.05). Conclusions: The TRG score can be used in practice when we want to compare the HR between the primary tumour and the PMs. The PRGS is a good measure of HR and is correlated with the efficacy of CT.